(untitled) - The World Bank (Hà Nội, 2007)
This report provides basic infrastrure, production and livelihood support service, and capacity-building support to predominantly ethnic minority communities living in Vietnam's poorest and most remote communes and villages.
Keywords: Developing countries,Viet Nam,Viet Nam; Economic conditions,Economic policy; Viet Nam